Blindsight - Cook, Robin (London PAN Books, 1993)
When a series of unrelated "yuppie" deaths by cocaine overdose are reported to the Medical Examiner's office, Dr Engler's curiosity is aroused. As the deceased's friends swear that their loved ones weren't involved with drugs, Dr Engler's curiosity intensifies. By the author of "Coma".
Keywords: Drug Abuse -- Visual Perception